Monetary institutions and the emergence of a new building type Fellner and Helmer's design for the Croatian Escompte Bank in Zagreb - Suljić, Azra; Šerman, Karin; Miklošević, Željka (2021)
In the late 19th and early 20th centuries, Zagreb witnessed the appearance of a new building typology meant to accommodate various sorts of monetary institutions: banks, savings banks, insurance companies and stock exchanges. This paper presents one important early example of that type – the seat of the Croatian Escompte Bank in Zagreb. It was designed in 1898-1899 by the Vienna-based studio Fellner and Helmer for a prominent location at 3 Ilica Street and it heralded the defining features of the new building type, such as the union of diverse facilities within a single structure, imposing architectural features and overall grand appearance, and a highly prominent role in the urban fabric of the city.In particular, it contributed to the definition of a spatial and formal scheme for commercial corner buildings, as the most exposed and attractive segments of downtown city blocks. In that sense it served as a productive model for a number of corner buildings intended for business purposes that were to follow.
Bibliografske bilješke uz tekst ; bibliografija i izvori: 41 jed.
Summary.
Keywords: Zgrade -- Tipologija zgrada -- Banke -- Monetarne institucije; 19./20. st; Zagreb